The Norm Cycle of the Global Economic Order with the Emergence of BRICS - Rahayu, Dini Septyana (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2025)
This study aims to describe the shift in the global political economy with the emergence of BRICS as part of the life cycle of international norms. As a global economic cooperation formed in June 2009, BRICS demonstrates its existence regardless of the different ideologies, identities, and interests of its member states. Although BRICS sparked discourse regarding its existence as an emerging power in the global political economy constellation, the participation of countries shows a positive trend. This study assumes that the inclusiveness, egalitarianism, democracy, and multipolarity plays as new norms. To analyze the shift in the global economic order with the emergence of BRICS, this study applies a qualitative research method with an interpretive approach. The Constructivist approach, norm life cycle by Martha Finnemore and Kathryn Sikkink, is used to describe the phenomenon. The results show that the shift in norms in the global economic order indicates the degree of norm promotion in the contestation of new global political economy norms which occurred due to the existence of BRICS. As norm entrepreneurs, BRICS promotes new norms through active socialization. However, BRICS institutionalization in NDB, CRA, and de-dollarization still require more substantial internalization to achieve the consolidation of the economic order.